Methodological study to classification of damage state immediately subsequent to the Banjarnegara Indonesia earthquake on 2018 - A. S., Bawono; Mohamad Idris, Ali; S., Kusumadew; Noram Irwan, Ramli (2019)
This paper presents a preliminary methodological study of a seismic risk assessment in a residential area to classification of damage state immediately subsequent after earthquake happen. This paper compared with difference research of a seismic risk assessment in the same area, i.e. Kertosari, Banjarnegara Indonesia. This methodological study to identified compatibility of the building vulnerability assessment with Naïve Bayes Classifier (NBC) method for determine the probability of damage that has 5 different damage statuses (slight, moderate, extensive, complete and none), where the criteria damage states in vulnerable building has additional damage parameters based on the latest building damage regulations issued in 2013, which have totally 104 data difference criteria. The results from determine the probability of damage processing using the NBC methodology in Kertosari Banjarnegara that most type of damage states is extensive damage. There is a difference with 2018 research data, where the most damage state is the moderate damage, and there is also a difference with the Banjarnegara Municipal Disaster Management Authority (BPBD Banjarnegara) data, which has the most damage state is the complete damage. The difference is caused by the criteria in determining the damage conditions are still too general and the uncertainty value is high. Therefore, it is necessary to improve and detailed the building type model and damaged condition criteria for Indonesian buildings, based on the assessment and suggestion of experts who have good and long experience in earthquake risk management and understand the state of damage to Indonesian building regulations, such as: (1) researchers/scientists; (2) small and medium-sized contractors; (3) construction supervisors; (4) government officials; (5) business leaders; (6) academics/educators; (7) non-governmental organizations, in order to obtain an assessment of damage to residential houses quickly and accurately.